Terrorism unjustified: the use and misuse of political power - Medina, Vicente (Rowman & Littlefield, 2015)
Dedication -- Acknowlegments -- Introduction -- Brief history of terrorism -- Disputing terrorism -- Critics of terrorism -- Apologists of terrorism -- "Whatever it takes" -- Postscript -- Notes -- Bibliography